Effects of TiC content on transverse rupture strength (TRS) of Cu-TiC composites produced using powder metallurgy (PM) technique - Islak, S.; Buytoz, S.; Eski, Ö. (National Institute of Optoelectronics, 2015)
Cu-TiC composites have been produced by powder metallurgy technique. Mixtures of Cu-TiC powders corresponding to weight fractions of 1, 3, 5, 10 and 15 wt.% TiC were hot-pressed for 4 min at 700 °C under an applied pressure of 50 MPa. The transverse rupture strength (TRS) of the composites was evaluated by a three-point bending test. SEM were used to analyze the resulting fracture surfaces from the bending test. The TRS decreased rapidly in the 0-5 wt.% TiC contents, while it decreased slowly in the 5-15 wt.% TiC contents. SEM results showed that with the increase in the addition of titanium carbide to copper matrix, pores and gaps were present in the structure.
Keywords: Cu-TiC; Metal matrix composites; Transverse rupture strength